Application of Box–Behnken design with response surface methodology for modeling and optimizing microwave-assisted hydro-distillation of essential oil from citrus reticulata blanco peel - Tran, Thien Hien; Dao, Tan Phat; Nguyen, Duy Chinh; Lam, Tri Duc; Do, Sy Trung; Toan, Tran Quoc; Thanh Huong, Nguyen Thi; Vo, Dai-Viet N.; Bach, Long Giang; Nguyen, Trinh Duy (IOP Publishing, 2019)
In this research, microwave-assisted hydro-distillation and Response Surface Methodology were selected for optimizing factors affecting the yield of essential oil from Citrus reticulate Blanco peels. This combined process was successfully modeled and optimized using a Box–Behnken design with response surface methodology (RSM). The effects of the material and water ratios, extraction time and microwave power on the extraction essential oils, efficiency of Citrus reticulata Blanco Peel were investigated. The optimal conditions for the Citrus reticulate Blanco peels oils yield were found to be a material and water ratios were 3.1:1mL/g, extraction time was 91.24 min, microwave power at 478 (W). Furthermore, analysis of variance indicated that the proposed quadratic model successfully interpreted the experimental data with coefficients of determination of the predicted R2 of 0.9909 concurred with the adjusted R2 of 0.9826. A confirmation test of the optimal conditions verified the validity of the model, yielding an essential oil efficiency of 5.5.